2009
DOI: 10.1016/j.envres.2008.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the risks and benefits of fish consumption: Individual choices to reduce risk and increase health benefits

Abstract: Studies of fish consumption often focus on awareness of and adherence to advisories, how much fish people eat, and contaminant levels in those fish. This paper examines knowledge and accuracy of risks and benefits of fish consumption among fishers and other recreationists in the New York Bight, indicative of whether they could make sound dietary decisions. While most respondents knew about health risks (70%) and benefits (94%) of consuming fish, far fewer could name specific risks and benefits. Less than 25% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 39 publications
2
72
2
Order By: Relevance
“…In particular, the bioaccumulation of Cd, arsenic (As), manganese (Mn), mercury (Hg) and lead (Pb) in the trophic food chain is the cause of concern since they can have deleterious effects on human health [35][36][37]. Furthermore, fish were one of the main links between the heavy metal present in the environment and the human exposure [38,39]. The results revealed that Cd concentrations were significantly increased in all the test tissues at all exposure periods.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the bioaccumulation of Cd, arsenic (As), manganese (Mn), mercury (Hg) and lead (Pb) in the trophic food chain is the cause of concern since they can have deleterious effects on human health [35][36][37]. Furthermore, fish were one of the main links between the heavy metal present in the environment and the human exposure [38,39]. The results revealed that Cd concentrations were significantly increased in all the test tissues at all exposure periods.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in various age groups have found that fish is perceived as a healthy food (Clonan, Holdsworth, Swift, Leibovici, & Wilson, 2011;Pieniak, Verbeke, & Scholderer, 2010), and many are aware that fish provides benefits to health (Burger & Gochfeld, 2009). Although there are emerging data relating to health behaviour and motives towards increasing fish and seafood intake (Verbeke, Sioen, Pieniak, Van Camp, & De Henauw, 2005;Olsen, Scholderer, Brunso, & Verbeke, 2007), there is limited information on consumers' knowledge and barriers towards fish consumption, and what predicts its consumption, particularly in older adults who are at greater risk for developing cardiovascular and related diseases (Australian Institute of Health and Welfare, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This was demonstrated in a study in which pregnant women who reported improved awareness of fish advisories, also admitted to higher frequencies of fish avoidance (22). Another study found that consumers lacked accurate information on contaminants in fish to make informed risk-balancing decisions (23).…”
Section: • Canned Tunamentioning
confidence: 99%